Age-related changes in behavior in C57BL/6J mice from young adulthood to middle age. Issue 1 (December 2016) - Shoji, Hirotaka; Takao, Keizo; Hattori, Satoko; Miyakawa, Tsuyoshi
Abstract Background Aging is considered to be associated with progressive changes in the brain and its associated sensory, motor, and cognitive functions. A large number of studies comparing young and aged animals have reported differences in various behaviors between age-cohorts, indicating behavioral dysfunctions related to aging. However, relatively little is known about behavioral changes from young adulthood to middle age, and the effect of age on behavior during the early stages of life remains to be understood. In order to investigate age-related changes in the behaviors of mice from young adulthood to middle age, we performed a large-scale analysis of the behavioral data obtained from our behavioral test battery involving 1739 C57BL/6J wild-type mice at 2–12 months of age. Results Significant behavioral differences between age groups (2–3-, 4–5-, 6–7-, and 8–12-month-old groups) were found in all the behavioral tests, including the light/dark transition, open field, elevated plus maze, rotarod, social interaction, prepulse inhibition, Porsolt forced swim, tail suspension, Barnes maze, and fear conditioning tests, except for the hot plate test. Compared with the 2–3-month-old group, the 4–5- and 6–7-month-old groups exhibited decreased locomotor activity to novel environments, motor function, acoustic startle response, social behavior, and depression-related behavior, increased prepulse inhibition, and deficits in spatial and cued fear memory. For most behaviors, the 8–12-month-old group showed similar but more pronounced changes in most of these behaviors compared with the younger age groups. Older groups exhibited increased anxiety-like behavior in the light/dark transition test whereas those groups showed seemingly decreased anxiety-like behavior measured by the elevated plus maze test. Conclusions The large-scale analysis of behavioral data from our battery of behavioral tests indicated age-related changes in a wide range of behaviors from young adulthood to middle age in C57BL/6J mice, though these results might have been influenced by possible confounding factors such as the time of day at testing and prior test experience. Our results also indicate that relatively narrow age differences can produce significant behavioral differences during adulthood in mice. These findings provide an insight into our understanding of the neurobiological processes underlying brain function and behavior that are subject to age-related changes in early to middle life. The findings also indicate that age is one of the critical factors to be carefully considered when designing behavioral tests and interpreting behavioral differences that might be induced by experimental manipulations.